Air pocket effects on air spindle vibrations in nanomachining. (March 2014) - Akhondzadeh, Mohammad; Vahdati, Mehrdad
In this study, factors that affect air spindle vibrations have been investigated experimentally. In order to achieve nanometer accuracies, the low vibration of air spindle is vital. Shape, size, depth, number of air pockets, and rotational speed of air spindles are important parameters influencing nanomachining vibrations. A total of 3 levels are selected for each parameter and in total 243 experiments have been performed. In this study, the rotor is considered externally which rotates about a central stator. Experiments were committed by the help of a lathe machine. For vibration measurements, the VibroTest 60 has been used. Results have been analyzed using the Design of Experiment method. From the results, it has been analyzed that the air spindle with 2 circular/rectangular air pockets and with 300 mm 2 area and 3 mm depth at a low rotational speed has minimum vibrations.